2018
DOI: 10.1002/jcp.27415
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs involved in PI3‐kinase signaling pathway in colorectal cancer

Abstract: In recent decades, cancer has been one of the most important concerns of the human community, which affects human life from many different ways, such as breast, lung, colorectal, prostate, and other cancers. Colorectal cancer is one of the most commonly diagnosed cancers in the world that has recently been introduced as the third leading cause of cancer deaths in the world. microRNAs have a very crucial role in tumorgenesis and prevention of cancer, which plays a significant role with influencing various facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…miRNAs are short non-coding RNAs that bind mRNAs, causing translation inhibition or transcript degradation, which ultimately results in a loss of PTEN expression and activation of the PI3K/Akt signaling cascade. Several miRNAs [61,62] and a complex of RBP known as Musashi-1/2 [63], targeting PTEN in CRC, have been identified. Therefore, modulation of those regulatory RNAs and RNA-binding proteins represent a therapeutic strategy aiming at restoring PTEN translation and expression, exploiting its antitumor activity and increasing cellular drug sensitivity.…”
Section: Pten As a Targetmentioning
confidence: 99%
“…miRNAs are short non-coding RNAs that bind mRNAs, causing translation inhibition or transcript degradation, which ultimately results in a loss of PTEN expression and activation of the PI3K/Akt signaling cascade. Several miRNAs [61,62] and a complex of RBP known as Musashi-1/2 [63], targeting PTEN in CRC, have been identified. Therefore, modulation of those regulatory RNAs and RNA-binding proteins represent a therapeutic strategy aiming at restoring PTEN translation and expression, exploiting its antitumor activity and increasing cellular drug sensitivity.…”
Section: Pten As a Targetmentioning
confidence: 99%
“…PTEN is a dominant cancer-suppressor gene blocking PI3K-Akt pathway via PIP3. Emerging evidence revealed PTEN deficiency, mutation or inexpression has been discovered in a lot of malignant tumors, such as the liver, breast, lung, brain, and prostate cancers [25,[39][40][41][42][43][44]. Our findings showed that the exosome-laden miR-155 directly targeted PTEN and lead to the decrease of respective target protein in recipient cells, and then activated the PI3K-Akt pathway.…”
Section: Discussionmentioning
confidence: 58%
“…Cancer has always been one of the most important issues affecting human life span and quality of life, which is considered as a bioheterogeneous disease caused by distinct abnormal changes in genetic material (Kumar & Sharawat, 2018; Noorolyai et al, 2019; Uscanga‐Palomeque et al, 2019). The American Association for Cancer Research (AACR) Cancer Progress Report 2019 indicated that 17 million people were diagnosed with cancer and 9.5 million died of cancer globally in 2018 (Sengupta & Honey, 2019).…”
Section: Introductionmentioning
confidence: 99%